Peningkatan Proses Pembelajaran Tematik Terpadu dengan Model Problem Based Learning di Kelas IV SDN 12 VII Koto Sungai Sariak - Hanif Faisal; Rahmatina Rahmatina; Muhammadi Muhammadi (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of the research is to describe the improvement of Integrated Thematic Learning Proccess by using Problem Based Learning Model at grade IV SDN 12 VII Koto Sungai Sariak. The subjects of the research were teachers (observers), researder ( practitioner) and the students grade IV SD Negeri 12 VII Koto Sungai Sariak. The result of the research showed that there was an improvement of integrated Thematic Learning process using PBL Model at cycle I and II. The Average of percentage of Teacher in designing Lesson plan improved from 74,5 % categorized fair to 95% categorized very good. The average a percentage of teachers’ activity improved from 75 % categorized fair to 94% categorized very good, Furthermare, the average of percentage of Students’ activity improved from 72,5% categorized fair to 95% categorized very good. Hence, Problem Based Learning model can improve students’ Integrated thematic learning process grade IV SDN 12 VII Koto Sungai Sariak.